Deacetylation of YAP1 Promotes the Resistance to Chemo- and Targeted Therapy in FLT3-ITD+ AML Cells - Feng, Panpan; Zhang, Jingru; Zhang, Juan; Liu, Xiaomin; Pan, Lina; Chen, Dawei; Ji, Min; Lu, Fei; Li, Peng; Li, Guosheng; Sun, Tao; Li, Jingxin; et al. (Frontiers in Cell and Developmental Biology, 2022)
The FLT3-ITD mutation occurs in about 30% of acute myeloid leukemia (AML) and is associated with poor prognosis. However, FLT3 inhibitors are only partially effective and prone to acquired resistance. Here, we identified Yes-associated protein 1 (YAP1) as a tumor suppressor in FLT3-ITD+ AML. YAP1 inactivation conferred FLT3-ITD+ AML cells resistance to chemo- and targeted therapy. Mass spectrometric assay revealed DNA damage repair gene poly (ADP-ribose) polymerase 1 (PARP1) might be the downstream of YAP1, and the pro-proliferative effect by YAP1 knockdown were partly reversed via PARP1 inhibitor. Importantly, histone deacetylase 10 (HDAC10) contributed to decreased YAP1 acetylation levels through histone H3 lysine 27 (H3K27) acetylation, leading to the reduced nuclear accumulation of YAP1. Selective HDAC10 inhibitor chidamide or HDAC10 knockdown activated YAP1, enhanced DNA damage and significantly attenuated FLT3-ITD+ AML cells resistance. Additionally, combination chidamide with FLT3 inhibitors or chemotherapy agents synergistically inhibited growth and increased apoptosis of FLT3-ITD+AML cell lines and acquired resistant cells from the relapse FLT3-ITD+ AML patients. These findings demonstrate that the HDAC10-YAP1-PARP1 axis maintains FLT3-ITD+ AML cells and targeting this axis might improve clinical outcomes in FLT3-ITD+ AML patients.